Analysis of a Single-Phase Transformer Protection Control System Using a Microcontroller: Analisis Sistem Kontrol Proteksi Transformator Satu Fase Menggunakan Mikrokontroler - Dwi Hadidjaja R.S.; Adriana Anteng Anggorowati; Dewi Handayani U.N (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Single-phase distribution transformers frequently experience overcurrent, overvoltage, and thermal stress, which account for a significant portion of operational failures in low-voltage networks. Specific Background: Conventional thermal–electromechanical relays exhibit slow response times (150–300 ms) and lack real-time multi-parameter monitoring, limiting their ability to prevent insulation degradation under rapidly fluctuating loads. Knowledge Gap: Prior microcontroller-based protection studies rarely provide quantitative benchmarking against conventional relays, lack integrated current–voltage–temperature sensing, and often omit controlled fault-injection experiments for latency validation. Aims: This study aims to develop and evaluate a microcontroller-based protection system using calibrated ACS712, ZMPT101B, and NTC sensors with real-time decision logic to reduce fault-detection latency and improve protection reliability. Results: Experimental testing on single-phase transformer fault-injection scenarios demonstrated detection latencies of 84 ms (overcurrent), 96 ms (overvoltage), and 112 ms (thermal), with sensor errors below 2.4%, a 98.1% trip success rate, and only 1.3% false positives across 50 cycles. Novelty: The system integrates low-error multi-parameter sensing with sub-120-ms response and provides the first quantitative benchmark showing performance improvements over conventional relays. Implications: Findings confirm that optimized low-cost microcontroller platforms can serve as scalable, accurate, and time-efficient protection solutions for distribution transformers, supporting future development of intelligent protection systems. Highlights: Sub-120 ms fault-detection latency significantly outperforms conventional relays. Multi-parameter sensing (current–voltage–temperature) enhances reliability and reduces missed trips. Low-cost microcontroller platform provides a scalable and accurate protection alternative for distribution systems. Keywords: Fault Detection, Microcontroller-Based Protection, Thermal Monitoring, Transformer Protection System, Overcurrent–Overvoltage